Improving SI Engines Performance to Obtain Lower Operating Cost and Emissions Using In-situ Produced HHO Gas - Eissa, Mohamed Shaban; Aissa, Walid Aniss; Mahmoud, Haroun Hassan; Abdel-Mohsen, Hesham Sayed (Applications of Modelling and Simulation, 2022)
Adding hydroxy (HHO) gas to the fuel of spark ignition (SI) engine is an effective way to improve the engine performance and to reduce its emissions due to several advantages of HHO gas over gasoline fuel. In the present study, a simple dry fuel cell was developed and tested. Sodium hydroxide and potassium hydroxide were used as catalysts in two different cells A and B. Each cell was connected to the intake manifold of single cylinder air-cooled SI engine that drives 32-m head centrifugal water pump. The engine performance was evaluated under different speeds and fully open water discharge throttle in three cases with and without adding HHO gas. The measured parameters considered were fuel consumption, pump flow rate, water head, exhaust temperature, intake air mass flow rate, and engine emissions including HC and CO gases. The results showed that cell B gave higher HHO production rate allocated with lower electric current compared to cell A. On average at different engine speeds, the engine efficiency increased by 20% and 23% by adding HHO gas from cell A and cell B, respectively. Moreover, adding HHO gas from cell A and B, respectively reduced brake specific fuel consumption by average values of 15% and 17%, increased relative air/fuel ratio by 12.72% and 13.76%, reduced CO emissions by 35.2% and 43.7%, and reduced HC emissions by 15.55% and 20%. The total operating costs when running the blended engine by HHO gas for 10,000 hours reduced to about 143 $ (cells A) and 195 $ (cells B).